Electroacupuncture relieves portal hypertension by improving vascular angiogenesis and linking gut microbiota in bile duct ligation rats - Huang, Po-Yu; Liu, Hsuan-Miao; Ko, Yan-Ru; Chang, Zi-Yu; Lee, Tzung-Yan (Frontiers in Microbiology, 2023)
The pathological increase in the intrahepatic resistance and decrease peripheral vascular tone in the development of portal hypertension (PHT). PHT has been linked to lower microbial diversity and weakened intestinal barrier, and interplay alters inflammatory signaling cascades. Electroacupuncture (EA) may ameliorate the inflammatory response and limit arterial vasodilatation and portal pressure. This study addresses the possible mechanisms underlying putative hemodynamics effects of EA in PHT rats. PHT was induced by bile duct ligation (BDL) over 7 days in rats. BDL rats were treated with low-frequency EA (2Hz) at acupoint, ST36, 10 min once daily for 7 consecutive days. EA significantly reduced portal pressure and enhanced maximum contractile responses in the aorta, and blunts the angiogenesis cascade in PHT rats. EA decreased the aortic angiogenesis signaling cascade, reflected by down-regulated of ICAM1, VCAM1, VEGFR1, and TGFβR2 levels. In addition, EA preserved claudin-1, occludin and ZO-1 levels in BDL-induced PHT model. Furthermore, EA demonstrates to have a positive effect on the gut Bacteroidetes/Firmicutes ratio and to reduce pro-inflammatory cytokines and endotoxins. These results summarize the potential role of EA in the gut microbiota could potentially lead to attenuate intestine injury which could further contribute to vascular reactivity in PHT rats.